Land fragmentation and consolidation in Albania - Lusho, Sherif; Papa, Dhimitër; Albania. Immovable Property Registration and Market Action Plan (Project) (Land Tenure Center, University of Wisconsin-Madison, 1998)
The 1945 agrarian reform in Albania changed the distribution of landownership. The land of the largest landlords was distributed to 70,000 families who either did not own any land or owned very little. Since this agrarian reform, land tenure structures have continually changed according to the organizational form of the agricultural sector. In the early 1990s, when the centralized economy was transformed into a market economy, landownership also had to change. Through the application of a 1991 law, approximately 383,000 families received about 500,000 hectares from the ex-cooperatives. In 1992, state-farm workers' families obtained the state-farm land. As a result of privatization, 480,000 farms were created. Land fragmentation is a relatively new phenomenon in Albania, but when privatization of agricultural land was concluded each family had a farm holding that was fragmented into many different parcels. Land fragmentation in Albania appears to be a spatial and territorial phenomenon, which means subdivision into many parcels of farmland that cannot support rational utilization of land. This paper concerns land fragmentation and consolidation in Albania after land privatization. The objectives of the paper are to provide information on the level of land fragmentation in the districts included in this study, determine the impacts of land fragmentation, explore methods of land consolidation based on both Albanian and foreign experience, and disseminate the information and conclusions throughout the country.
iv, 39 p.
Keywords: Consolidation of land holdings Albania; Farms, Size of Albania; Farms, Small Albania; Fragmentation of land holdings Albania; Agrarian structure Albania